Low Digestive Hemorrhages due to Angiodysplasia - Harretche, Martín; Armand Ugon, Alfredo; Baglivi, Nicolás; Rocca, Guillermo (Cirugía del Uruguay, 1980)
The paper describes the manner of treating low digestive hemorrhages, highlighting the importance of angiodysplasias as the cause of bleeding in patients suffering from other pathologies, such as diverticulitis. It also refers to methods for establishing diagnosis and their application; to the different symptoms in patients with angiodysplasias and, finally, to the conduct to be followed in each case.